The efficacy of social skills training for individuals with schizophrenia - Ντούσια Παρασκευή; Κατσαμάγκος Αντώνης; Οικονόμου Μαρίνα (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Ten individuals with schizophrenia and two with schizoaffective disorder received group training in social skills, including conversation skills, friendship skills, and dating skills as well as problem-solving skills. The training, coupled with case management, was administered twice per week for one hour each session for a total of 5 months. The primary outcome measures were the Social Contact and Communication subscales of the Life Skills Profile, the WHOQOL-BREF, and the Self-efficacy/self-esteem subscale of the Empowerment Scale. Based on these, participants’ social functioning, community functioning, and self-efficacy perceptions were assessed respectively. Measures were taken at pre-treatment and post-treatment. Patients’ social functioning and community functioning improved over time whereas self-efficacy beliefs did not significantly change. Patients who completed homework assignments frequently improved more in social contact compared to patients who completed homework assignments infrequently. Findings suggest that social skills training for outpatients with chronic mental illness leads to acquisition of social skills that are important in everyday life. Case management is a critical aspect of treatment that enhances learning and transfer of social skills outside the immediate training setting. Benefits from social skills homework assignments mainly depend on the type of homework.